Coupled effect of temperature and stress on the microstructure and stress rupture behavior of 9% Cr-CrMoV dissimilar welded joints. (February 2022) - Wu, Guanzhi; Ding, Kai; Wei, Tao; Liu, Xia; Fan, Manjie; He, Yi; Huo, Xin; Gao, Yulai
Highlights: The CrMoV-HAZ is the weakest zone in the 9% Cr-CrMoV welded joint. Elevated temperature can induce the formation and growth of the brittle precipitates. The voids are initiated by mismatch deformation between the precipitates and matrix. Abstract: Based on the practical application requirements, the weld rotor was chosen as a preferable candidate to adapt to the higher steam temperature. In this study, the rupture behavior and fracture mode for the 9% Cr-CrMoV dissimilar welded joints are investigated. The specimens both rupture in the heat affected zone of CrMoV steel with a ductile rupture mode. The rupture time of the specimen under lower stress at higher temperature is shorter than that under higher stress at lower temperature. Additionally, the microstructure observation shows that the increased temperature can accelerate the precipitation and growth of the second phase particles. The micro-voids caused by these particles can reduce the ductility of the welded joint and resultantly lead to the premature fracture.